The Advertising advantage. (Harvard business review paperback series ;, 1991)
This collection of "Harvard Business Review" articles argues that, beneath the glamour of advertising, lies the grit of hard-nosed management. There are articles on maintaining market share, the perils of comparative ads, when to advertise your company, and research on ad techniques that work.